Differential response of wheat genotypes in relation to phosphorus in the soil - Renato Ben, José; Dechen, Antonio Roque (Pesquisa Agropecuaria Brasileira, 1998)
The low phosphorus availability of Brazilizan soils, the high cost of fertilization and the condition of a natural resource not renewable motivated the development of a breeding program at Embrapa-CNPT, aiming at obtaining genotypes with efficiency in the use of soil phosphorus. Genotypes were obtained by backcrossing recurrent cultivars BH 1146, Nobre, Tucunduva 2-78, IAS 55, and Londrina with the cultivar Toropi and were selected in a high acid, phosphorus deficient soil. In this study the genotypes were evaluated in relation to phosphorus, in an environment provided with wire screening, in a Dark Red Latosol (Haplortox) of the Passo Fundo mapping unit, both in the presence and absence of 120 mg/kg of P2O5. The evaluations were carried out based on the production of dry matter of above-ground parts of plants harvested at flowering stage. The controls were the parent materials. Crosses between the cultivar Toropi, less responsive to phosphorus, and cultivars BH 1146, Nobre, and Tucunduva 2-78, more responsives to phosphorus, originated genotypes with intermediate responses to phosphorus as compared to the parents. Genotypes from the crosses of the cultivar Toropi with cultivars IAS 55 and Londrina, which showed responses to phosphorus equal to or higher than Toropi, showed tendency to present higher responses to phosphorus than those observed for the parents.
Keywords: Triticum aestivum; phosphorus fertilization; plant breeding